2013
DOI: 10.3390/ijerph10105026
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Its Associated Factors in 13-Year-Old Urban Adolescents

Abstract: The available estimates reveal that 20–50% of adolescents report depressive symptoms, being one of the most prevalent health problems in adolescence. The aim of this study was to assess the prevalence of depressive symptoms in a community sample of 13-year-old adolescents and identify associated features. Thirteen year-old adolescents attending private and public schools in Porto (n = 1,988, 52.2% females) were evaluated from October 2003 to June 2004 and completed a questionnaire including health behaviors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Depressive disorders at adulthood has a precursor from tender age most especially during adolescence [20,21]. Kim-Cohen et al [22] in their study among 1,037 who were followed for 26 years found that only 25% of their participant experienced depression at adulthood while 75% of adults who met criteria for major depression, had earlier experienced depressive disorder in childhood or adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Depressive disorders at adulthood has a precursor from tender age most especially during adolescence [20,21]. Kim-Cohen et al [22] in their study among 1,037 who were followed for 26 years found that only 25% of their participant experienced depression at adulthood while 75% of adults who met criteria for major depression, had earlier experienced depressive disorder in childhood or adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies measured educational level in parents as a separate measure (5,33,35), whereby only one of them (35) found a significant association between parental education and depressive symptoms among girls. Two studies measured Family Affluence Scale (FAS) (16,34), whereby only one found a significant association between FAS and depressive symptoms (16).…”
Section: Results By Socioeconomic Statusmentioning
confidence: 99%
“…Four studies included parental education as a SES measure; Bulhões et al (33) and Frojd et al (5) did not find a significant social gradient, while Gore et al (35) and Torikka et al (17) found a significant social gradient. Gore et al (35) used the Center for Epidemiologic Studies' Depression Scale (CES-D), with a cut-off score of 24 that indicated clinical depression for adolescent girls.…”
Section: Comparisons Of Studies With Parental Educational Level or Famentioning
confidence: 99%
See 2 more Smart Citations